PENGELOLAAN HUTAN RIMBO TUJUH DANAU OLEH MASYARAKAT HUKUM ADAT DI DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Annisya Milenia Ramadhani; Hayatul Ismi; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Customary forest is a forest that is in the territory of customary lawcommunities and is a high heritage and is jointly owned by the adat community.Buluh Cina Village Tourism Forest is a customary right or what is called the RimboSeven Lakes Customary Forest which is managed by the Indigenous People ofBuluh Cina Village together with the Traditional Institution of Buluh Cina Village,Siak Hulu District, Kampar Regency. The Buluh Cina Village Government and thecommunity should be able to work together in protecting the existing customaryforest. The purpose of this thesis research is first, to find out the management ofthe Rimbo Tujuh Danau Customary Forest by the customary law communitythrough its existence in Buluh Cina Villageand to find out what are the obstacles inmanaging the Rimbo Tujuh Danau Customary Forest by the customary lawcommunity in Buluh China Village.This type of research is sociological legal research conducted in Buluh CinaVillage, Siak Hulu District, Kampar Regency, Riau Province. By using primary,secondary and tertiary data sources. Data collection techniques with interviewsand library research. Data processing was carried out qualitatively, namely datapresented in the form of discussions and presented in sentences.The results of this study indicate that the management of the Rimbo TujuhDanau customary forest by indigenous peoples through their existence in BuluhCina Village is known to have implemented customary regulations to preserve thecustomary forest they own. To maintain this existence, the people who live in theRimbo Tujuh Danau Customary Forest area carry out activities such as Maawuo(Fishing), Maintaining Forests, Maintaining Lakes, Using Traditional FishingEquipment and Using Fruit Trees and Medicinal Plants. Obstacles in themanagement of the Rimbo Tujuh Danau Customary Forest by the customary lawcommunity in Buluh Cina Village include land clearing without permits in theRimbo Tujuh Danau Customary Forest area, Extraction of timber and non-timberforest products such as illegal logging and hunting, The potential for forest fires.Keywords: Customary Law, Customary Forest, Buluh Cina Village